An Apparent Effect Of Size Distribution Of FVIIIR: Ag Multimers On Immunoradiometric Assays - Lamb, M A; Reisner, H M; Cooper, H A; Wagner, R H (Thrombosis and Haemostasis, 1981)
Immunoradiometric assays (IRMA) of FVIIIR: Ag from normal and certain variant VWD plasmas have suggested possible antigenic differences in the molecules. Studies reported thus far have used antibody specific for normal FVIIIR: Ag. We have further studied this question of antigenic differences using 2 populations of antibody isolated from an antisera prepared against highly purified human FVIII. Isolated IgG was labeled with [125-I]. The population of labeled IgG “specific” for variant FVIIIR: Ag was separated by immune complex formation with a VWD plasma previously shown, by 2% agarose crossed immunoelectrophoresis, to contain only the lower molecular weight multimers of FVIIIR: Ag. The “specific” labeled IgG was obtained by low pH dissociation and subsequent G-200 chromatography. [125-I] IgG “specific” for normal FVIIIR: Ag was similarly obtained after immune complex formation with pooled normal human plasma. Liquid phase IRMAs were performed using differential precipitation with ammonium sulfate or PEG to separate antigen-antibody complexes from free antibody. Using antibody “specific” for normal FVIIIR: Ag, a lack of parallelism was noted in the dose-response curves of variant plasmas as well as a decrease in maximum antibody bound, as compared to normal. Interestingly, when this antibody was absorbed with the variant VWD plasma and the remaining antibody used in IRMAs, none was bound by either variant or normal plasma.Using antibody “specific” for variant FVIIIR: Ag, a similar lack of parallelism in dose-response curves and a decrease in maximum antibody bound were observed. Therefore rather than antigenic differences as previously implied, these results suggest that the discrepancies noted in IRMAs of variant and normal plasmas are a function of the size of the FVIIIR: Ag multimers.